Odpowiedzi

Najlepsza Odpowiedź!
2010-02-21T11:22:05+01:00
A. (x-2)-(2-x) = x-2-2+x= 2x-4

b. (a+b)+(2a-b)-(a-2b) = a+b+2a-b-a+2b = 2a+2b

c. (3x-y+1)-(x+y)+(y-x) = 3x-y+1-x-y+y-x = x-y+1

d. -(2a² -3ab)-(2b-3a²)+(-ab-b) = -2a²+3ab-2b+3a²-ab-b= a²+2ab-3b
1 4 1
2010-02-21T11:23:54+01:00
A.
(x-2)-(2-x)=x-2-2+x=2x-4

b.
(a+b)+(2a-b)-(a-2b)=a+b+2a-b-a+2b=2a+2b

c.
(3x-y+1)-(x+y)+(y-x)= 3x-y+1-x-y+y-x=x-2y+1

d.
-(2a do kwadratu -3ab)-(2b-3a do kwadratu)+(-ab-b) =-2a^2+3ab-2b+3a^2-ab-b=
= a^2+2ab-3b
2 5 2
2010-02-21T11:23:55+01:00
A) x-2-2+x=2x-4
b) a+b+2a-b-a+2b=2a+2b
c) 3x-y+1-x-y+y-x=x-y+1
d)-2a(dopotegi2) + 3ab - 2b +3a(dopotegi2) -ab-b=a(dopotegi2) +2ab-3b
1 5 1